Early pregnancy failure as a training tool for chorionic villus sampling. (30th August 2013) - Nicholas, Sara; Orzechowski, Kelly; Potti, Sushma; Baxter, Jason; Berghella, Vincenzo; Weiner, Stuart
Abstract: Objectives: The goal of this study is to evaluate the success of a training program in chorionic villus sampling (CVS) of early pregnancy failure (EPF) for maternal‐fetal medicine (MFM) fellows. Methods: We conducted a retrospective review of a new training program in CVS for MFM fellows. Women with EPF up to 13 weeks estimated gestational age were offered inclusion in our program and counseled on alternatives. Transcervical CVS was performed for both fellow education and cytogenetic diagnosis. The primary outcome was a successful diagnosis, and the secondary outcome was cell growth by fellow experience. Results: Thirty‐nine patients diagnosed with EPF from December 2011 to March 2013 underwent CVS. Villi obtained via CVS yielded a diagnosis in 62% of cases. CVS samples with successful karyotype had more villi but were otherwise similar. CVS by experience showed a trend towards increased success and villi volume after the first five procedures. Abnormal results were obtained in 72% of cases, 15% of which led to changes in care. Conclusion: CVS of EPF is an option for the training of MFM fellows as it was acceptable to most patients, and the majority of CVS specimens yielded a karyotype diagnosis. © 2013 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? CVS training can be difficult, as it often requires simulation on noncontinuing pregnancies to attain proficiency. Fewer providers are completing fellowship with adequate CVS training. What does this study add? Early pregnancy failures provide an excellent resource for CVS training while serving as a diagnostic tool for patients.